ON SOME ASPECTS OF THE STUDY OF PULVERIZED COAL AND FUEL MIXTURES COMBUSTION IN A DROP TUBE FURNACE (Modern Problems of Metallurgy, 2021)
The article considers some aspects of the pulverized fuel combustion modelling in the laboratory on installations called vertical tube furnaces (referred to as drop tube furnaces in scientific periodicals). We have considered the scheme of the installation to study the process of pulverized coal (PС) combustion in conditions similar to the conditions of heating and ignition of coal particles in the blast flow of the blast furnace and their subsequent gasification in the raceway. We have formulated the basic requirements for ensuring the reliability of modelling results. We have examined the methods of combustion completeness (burnout) estimation used in similar studies. We have proposed a convenient method for the estimation of the burnout of two-component fuel mixtures. According to this method, the estimation can be performed for any ratio of components in a two-component fuel mixture with the use of data on the initial ash content in each of them and the relevant burnout. We have obtained the estimated data on the dependence of the burnout of PC (anthracite, lean coal) with fuel additives. It has been shown that the proposed approach can be used to evaluate experimental data regarding the study of the combustion completeness of fuel mixtures. It has been established that for the initial stages of PC combustion (heating, emission and ignition of volatile matters), which occur before the fuel particles enter the blast furnace raceway, the fuel mixtures burnout values recorded in the experiments do not differ significantly from the estimated ones. For the final stages of PC combustion (heating and burnout of char), which occur mainly in the raceway and outside, the combustion completeness determined in laboratory studies was significantly higher than the estimated one. The obtained results confirmed the efficiency in the use of drop tube furnace to model the PC combustion process during the fuel injection with the heated blast flow in the blast furnace raceways and study of the influence of various factors on the combustion process. The results of such studies can be used to improve the design of PC injection units in the blast furnace and to study the possibilities for improving the coal particles combustion completeness and the specific consumption of PC.